Mapping the Efficiency of Health Services in Indonesia to Mitigate Scarring Effect Due to the Covid-19 Pandemic - Hastarini Dwi Atmanti; An’im Kafabih (Cita Konsultindo Research Center, 2023)
The purpose of this article is to map the efficiency of health services in Indonesia before the Covid-19 pandemic (2017-2018) and during the pandemic (2019-2021). The analytical method used is Data Envelopment Analysis (DEA) using Banxia Frontier 3 software. This relative efficiency measurement covers provinces in Indonesia. The input variables used are the number of Public Health Centers, the number of hospitals, the number of medical personnel at public health centers, the number of medical personnel in hospitals and the realization of deconcentration funds in the health sector per province in Indonesia. The impact of the pandemic due to Covid-19 has the potential to cause a scarring effect in the future, so the need to mitigate the scarring effect of the covid pandemic on the national economy is urgently needed not only by developed countries, but developing countries like Indonesia. The health sector is urgently needed, especially during the Covid-19 pandemic. The readiness of the health sector in dealing with patients is urgently needed. The performance of health services in Indonesia, as shown by the efficiency of health services in Indonesia, is still inefficient. This article maps the efficiency of health services before and during the Covid-19 pandemic, so that we can see the readiness of health services to handle the Covid case. This is important to mitigate the scarring effect so that the national economy recovers.